High-frequency heart rate avriability is prospectively associated with sleep complaints in a healthy working cohort - Cribbet, Matthew R.; Thayer, Julian F.; Jarczok, Marc N.; Fischer, Joachim E. (Psychosomatic medicine, 2024)
Objective - Vagus nerve functioning, as indexed by high-frequency heart rate variability (HF-HRV), has been implicated in a wide range of mental and physical health conditions, including sleep complaints. This study aimed to test associations between HF-HRV measured during sleep (sleep HF-HRV) and subjective sleep complaints 4 years later. Methods - One hundred forty-three healthy employees (91% male; MAge = 47.8 years [time 2], SD = 8.3 years) of an industrial company in Southern Germany completed the Jenkins Sleep Problems Scale, participated in a voluntary health assessment, and were given a 24-hour ambulatory heart rate recording device in 2007. Employees returned for a health assessment and completed the Jenkins Sleep Problems Scale 4 years later. Results - Hierarchical regression analyses showed that lower sleep HF-HRV measured in 2007 was associated with higher self-reported sleep complaints 4 years later after controlling for covariates (rab,c = −0.096, b = −0.108, 95% CI, −0.298 to 0.081, ΔR2 = 0.009, p = .050). - Conclusions - These data are the first to show that lower sleep HF-HRV predicted worse sleep 4 years later, highlighting the importance of vagus nerve functioning in adaptability and health.
Gesehen am 15.11.2024